Hospital Services Quality From Patients\' Point Of View: A Cross-Sectional Study In Tehran Private Hospitals - Ehsan Zarei; Seyed Mahmud Ghazi Tabatabai; Abbas Rahimi Forushani; Arash Rashidiyan; Mohammad Arab (Tehran University of Medical Sciences, 2012)
Background and Aim: Over the past decade, the number of private centers providing health care services in Iran has had a continuous growth and the highly competitive market in private hospitals industry has caused increasing pressure on them to provide services with a higher quality. The purpose of this study was to assess the quality of services being provided in private hospitals of Tehran as judged by patients. Materials and Methods: This cross-sectional study was conducted in 2010 in Tehran. The study sample comprised 983 patients, randomly selected from 8 private hospitals. The survey instrument was the standard SERVQUAL questionnaire. Wilcoxon, t-test, and Kruskal-Wallis tests were used for statistical analyses. Results: The total mean scores of patients' expectation and perception were 4.92 and 4.02, respectively. The highest figures were related to the tangible factors dimension and the lowest ones to the empathy dimension. The differences between the perception and expectation for all the 22 items and the 5 dimensions were found to be statistically significant(p< 0.001). Conclusion: SERVQUAL is valid and reliable in hospital settings as a standard tool for the assessment of quality. The results of the present study have revealed the areas that need to be improved as far as the patients are concerned. Measuring the opinion of patients can help facilitate the provision of hospital services, and improve the quality of such services and patients' satisfaction.